In Silico Modeling of the Antiplatelet Pharmacodynamics of Low‐dose Aspirin in Health and Disease. Issue 5 (30th May 2017) - Giaretta, A; Rocca, B; Di Camillo, B; Toffolo, GM; Patrono, C
Abstract : The influence of platelet turnover on cyclooxygenase (COX‐1) inhibition by low‐dose aspirin remains largely uncharacterized due to limited feasibility of studying aspirin pharmacodynamics in bone marrow precursors. We developed an in silico compartmental model describing the aspirin effects on COX‐1 activity in a population of megakaryocytes (MK) and in peripheral platelets. Model parameters were inferred from the literature and calibrated using measurements of serum thromboxane B2 (sTXB2 ), as proxy of COX‐1 activity in peripheral platelets, in 17 healthy subjects and 24 patients with essential thrombocythemia (ET). The model reproduced well the average time‐course of sTXB2 inhibition in healthy (accuracy = 10.4%), the reduced inhibition of sTXB2 observed in ET, and the effect of different dosing regimens. In conclusion, the in silico model accurately describes COX‐1 inactivation by low‐dose aspirin in MK and platelets in different clinical settings, and might help personalize aspirin regimens in conditions of altered megakaryopoiesis.